Analisis Pengaruh Keberagaman Produk, Persepsi Harga, Promosi Penjualan Terhadap Kepuasan Konsumen Hypermartket Pakuwon Supermall Di Surabaya - Rena Febrita Sarie (STIE Mandala Jember, 2018)
The purpose of this study is to analyze ans examine the impact of the variety of the product, price perception, sales promotion towards customer satisfaction of hypermarket Pakuwon Supermall in Surabaya. This research is a confirmatory research or conclusive research, which highlights the relationship between the research variables and tests the formulated hypotheses. The sampling technique used in this study is a purposive random sampling. This result of the study showed that sales promotion showed significant positive effect towards customer satisfaction Hypermarket Pakuwon Supermall in Surabaya. Keywords: Variety of the product, Price Perception, Sales Promotion and Customer Satisfaction.